EX ANTE v. EX POST PROTECTION: the implementation Of collaterals in financing transaction - Escobar Rozas, Freddy (2017)
Collaterals are actives (material and immaterial) that act as warrants against any financial operation. This figure allows to reduce risks related to financial operations throughout credit qualification of the protected agent. For this reason, an adequate regulation of its execution (ex ante and ex post) is useful to reduce situations originated by information asymmetry.In this article, the autor develops the legal treatment of this juridical figure and its applicable regimens, analyzing the juridical and economic implications of the two ways to protect its execution: juridical proceedings (ex ante) and extra juridical proceedings (ex post).